Pérdidas en prefabricados de hormigón, sujeto de estudio Mutualista Pichincha - Gaibor Cujilema, José Luis (2022)
The “ready-made house” system of the Mutualista Pichincha Company offers to their clients top-quality housing and the fast assembly. Its dispatch depends on the production phase of the prefabricated elements and the final assembly phase of the product. The objective of this research work is to identify the existing waste in both mentioned phases, through the application of lean tools. For this purpose, a visual analysis of the current operation managed by the company was carried out. The data obtained allowed the calculation of productive and unproductive time and the classification of activities that add value (AV) and that do not add value (NAV), for a clearer vision of what happens within the processes, a value stream mapping was developed. (VSM) current where existing waste is distinguished and this gave way to the search for tools that help reduce or eliminate such waste. From this analysis in which the errors in the processes were identified, strategies were established to improve them and the future VSM was proposed.